Pengembangan Modul PAI Berbasis Nilai Keadilan Islam Wasathiyah Pada Siswa Kelas XI - Juwariyah, Juwariyah; Zulfah, Machnunah Ani (JoEMS (Journal of Education and Management Studies), 2023)
The fact that radicalism has spread in education, especially in schools. Whether we realize it or not, these intolerant actions become the seeds for the emergence of radicalism, that have the potential to give rise to violence and are contrary to educational norms. One of the efforts to prevent radicalism in schools is to provide students with an understanding of the values ​​of justice in Wasathiyah Islam. The aim of this research is to determine the effectiveness of the teaching materials developed in increasing students' interest in learning at SMAN Kabuh using research and development methods, or also known as Research and Development. Research and development methods are used to produce and test the effectiveness of these products. This development uses the development model from Gagne & Briggs which consists of 12 steps. The data sources used are primary data and secondary data, the primary data are teachers in PAI subjects and class XI students, the secondary data is documentation. The results of research using pre-test and post-test questionnaires show that the product developed in the form of PAI Modules has a feasibility of 80.4%, so the teaching materials developed are very effective in increasing students' interest in PAI lessons.